ANTIBIOTIC RESISTANT ORGANISM: AN EMERGING PUBLIC HEALTH PROBLEM AND ROLE OF AYURVEDA (AN OVERVIEW) - Sharma, Chakrapany; Singh, Chandan; Narayan Sharma, Laxmi; Purvia, Rajendra; Adlakha, Manoj (International Journal of Ayurveda and Pharma Research, 2015)
Antibiotic resistance is a serious and growing phenomenon in contemporary medicine and has emerged as one of the pre-eminent public health concerns of the 21st century. Antibiotic resistance is a form of drug resistance whereby some (or, less commonly, all) sub-populations of a microorganism, usually a bacterial species, are able to survive after exposure to one or more antibiotics; pathogens resistant to multiple antibiotics are considered multidrug resistant (MDR) or, more colloquially, superbugs. However, the increasing prevalence of antibiotic-resistant bacterial infections seen in clinical practice stems from antibiotic use both within human medicine and veterinary medicine. According to a new report by the U.S. Centers for Disease Control and Prevention (CDC), at least 2 million people in the United States develop serious bacterial infections that are resistant to one or more types of antibiotics each year, and at least 23,000 die from the infections. Ayurveda refers that the Dosha get aggravated by exogenous or endogenous causes, which further spread in body by the using improper foods and activities. It vitiates kosthagni (Metabolic enzymes) which leads to improper digestion production of Ama (toxin) and their minute Srotas (body channels) this is called shrotodushtie (Disequilibrium in channels). When the Rasadhatu (plasma and lymph) containing Ama (toxin) and aggravated Doshas reaches the place where Kha Vaigunya (movement tendency towards empty space) has taken place, it being unable to get into the minute channels, gets obstructed, stagnates/accumulates there and gives rise to such diseases caused by exogenous causes. That is why, Ayurveda advocates enhancing the immunity against the diseases. Several plant extracts have exhibited synergistic activity against microorganisms. The Indian plants possessing significant anti-microbial activity are Neem (Azadirachta indica), Pippali (Piper longum), Guduchi stem (Tinospora cordifolia) and Amla fruit (Emblica officinalis), among others. The purpose of this paper is to outline possible ways in which certain concepts of Ayurveda can be used for finding remedy of emerging health problem The Antibiotic Resistant Organism.